2012
DOI: 10.1016/j.geomorph.2012.03.023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vegetation patterns on wind-blown mass transport at the regional scale: A wind tunnel experiment

Abstract: Wind erosion is a global environmental problem. Re-vegetating land is a commonly used method to reduce the negative effects of wind erosion. However, there is limited knowledge on the effect of vegetation pattern on wind-blown mass transport. The objective of this study was to investigate the effect of vegetation pattern on this phenomenon within a land unit and at the border between land units. Wind tunnel experiments were conducted with artificial shrubs representing Atriplex halimus. Wind runs at a speed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 50 publications
3
49
1
Order By: Relevance
“…New approaches to resolve the partition of wind momentum fluxes over heterogeneous land surfaces (see Section 3.2.1) may provide opportunities to reduce the uncertainty in sediment deposition schemes. Theoretical calculations [57,58] and experimental measurements [46,54,62,63,79,90] suggest that protective wakes downwind of individual vegetation elements extend to approximately 7-10 h (where h is the height of the element). However, this can vary significantly depending on plant porosity, pliability and configuration.…”
Section: Trapping Of Windborne Sedimentmentioning
confidence: 99%
See 3 more Smart Citations
“…New approaches to resolve the partition of wind momentum fluxes over heterogeneous land surfaces (see Section 3.2.1) may provide opportunities to reduce the uncertainty in sediment deposition schemes. Theoretical calculations [57,58] and experimental measurements [46,54,62,63,79,90] suggest that protective wakes downwind of individual vegetation elements extend to approximately 7-10 h (where h is the height of the element). However, this can vary significantly depending on plant porosity, pliability and configuration.…”
Section: Trapping Of Windborne Sedimentmentioning
confidence: 99%
“…Wu et al [62] also showed that using multiple vegetation species can provide optimal sheltering effects. There is little research on the impact of vegetation patch configuration at the meso scale, with the exception of some scaled-down wind tunnel experiments [60,78,79] and modelling studies of forest edges [81][82][83]. Wind tunnel and modelling experiments have also been used to understand flow behaviour around backward-facing steps (e.g., [84,85]), although these configurations often have more extensive low-velocity zones and delayed reattachment points compared to vegetated cases, due to their almost parallel-to-wall streamlines.…”
Section: Trapping Of Windborne Sedimentmentioning
confidence: 99%
See 2 more Smart Citations
“…Udo and Takewaka (2007), in their wind tunnel experiments, concluded that, in addition to density, the height and flexibility of vegetation are essential in determining the effectiveness in decreasing mass transport by wind. Youssef et al (2012) suggested that the pattern of vegetation in parallel rows to the predominant wind direction lowers total mass transport.…”
Section: Introductionmentioning
confidence: 99%